Hidden hunger and the transformation of food systems : how to combat the double burden of malnutrition? - International Congress Hidden Hunger 2019 : Stuttgart, Germany); Biesalski, Hans Konrad 1949- (Basel : Karger, 2020)
Hidden hunger is not about providing enough calories, it is about a lack of micronutrients, which has life-long consequences for the children who are mostly affected. This begins with physical and cognitive developmental disorders and continues with an increased risk of non-communicable diseases and the occurrence of obesity. The book compiles the contributions of the Fourth Congress on Hidden Hunger 2019 as original articles. The focus of the congress was the problem of malnutrition and overweight, which can coexist and is termed a "double burden". Part of the book deals with the causes of malnutrition and the challenge of achieving an agricultural system that is more focused on food quality. Another part discusses the causes and intervention approaches to tackling childhood obesity, especially in connection with malnutrition. All in all, this publication is a summary of important work by highly renowned authors on the topic of the congress: "Hidden Hunger and the Transformation of Food Systems: How to Combat the Double Burden of Malnutrition?" Like its two predecessors, the book fills an important gap by summarizing the essential aspects for science, applied research, and politics at a high level.
Keywords: NUTRICIÓN -- CONGRESOS; DESNUTRICIÓN -- CONGRESOS; DESNUTRICIÓN -- PREVENCIÓN -- CONGRESOS; HAMBRE -- CONGRESOS